2017
DOI: 10.1039/c6cp07487a
|View full text |Cite
|
Sign up to set email alerts
|

The radio spectra of planar aromatic heterocycles: how to quantify and predict the negative inertial defects

Abstract: The simplest tricyclic aromatic nitrogen heterocyclic molecules 5,6-benzoquinoline and 7,8-benzoquinoline are possible candidates for detection of aromatic systems in the interstellar medium. Therefore the pure rotational spectra have been recorded using frequency-scanned Stark modulated, jet-cooled millimetre wave absorption spectroscopy (48-87 GHz) and Fourier Transform Microwave (FT-MW) spectroscopy (2-26 GHz) of a supersonic rotationally cold molecular jet. Guided by theoretical molecular orbital predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…However, it has been observed that PAHs usually have a small negative value of the inertial defect due to the dominant effect of low-frequency out-of-plane vibrations. [33][34][35] The value of 1,4-NQ inertial defect is Δ = I c À I a À I b = À 0.4268(2) uÅ 2 . The value obtained for 1,4-NQ can be compared with some of similar systems such as naphthalene (À 0.137 uÅ 2 ), [35] azulene (À 0.152 uÅ 2 ), [36] trans-1-hydroxynaphthalene (À 0.212 uÅ 2 ), [37] cis-2-hydroxynaphthalene (À 0.237 uÅ 2 ), [37] cis-1-naphthaldehyde Table 1.…”
Section: Inertial Defectmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it has been observed that PAHs usually have a small negative value of the inertial defect due to the dominant effect of low-frequency out-of-plane vibrations. [33][34][35] The value of 1,4-NQ inertial defect is Δ = I c À I a À I b = À 0.4268(2) uÅ 2 . The value obtained for 1,4-NQ can be compared with some of similar systems such as naphthalene (À 0.137 uÅ 2 ), [35] azulene (À 0.152 uÅ 2 ), [36] trans-1-hydroxynaphthalene (À 0.212 uÅ 2 ), [37] cis-2-hydroxynaphthalene (À 0.237 uÅ 2 ), [37] cis-1-naphthaldehyde Table 1.…”
Section: Inertial Defectmentioning
confidence: 99%
“…[33][34][35] The value of 1,4-NQ inertial defect is Δ = I c À I a À I b = À 0.4268(2) uÅ 2 . The value obtained for 1,4-NQ can be compared with some of similar systems such as naphthalene (À 0.137 uÅ 2 ), [35] azulene (À 0.152 uÅ 2 ), [36] trans-1-hydroxynaphthalene (À 0.212 uÅ 2 ), [37] cis-2-hydroxynaphthalene (À 0.237 uÅ 2 ), [37] cis-1-naphthaldehyde Table 1. Theoretical spectroscopic parameters of 1,4-NQ using the 6-311 [c] (D) y/n/n y/n/n y/n/n y/n/n y/n/n y/n/n y/n/n N [d] 44 21 1.9 0.7 0.7 0.6 1.0 0.7 1.5…”
Section: Inertial Defectmentioning
confidence: 99%
See 3 more Smart Citations